The success or failure rates of dental implants as assessed by implantologists - Angeles, Karla Monina Veluz; Vinco, Ellen Francis C.
Nowadays, the use of dental implants as an alternative treatment in replacing missing tooth structures has become more acceptable. This study aimed to determine the success or failure rates of dental implants in Metro Manila based on the assessment of implantologists. Thirteen out of twenty dentists who were doing implants were sent questionnaires regarding patient information and dental implant status. The dental implant was assessed using the following criterion: pain, chewing difficulty, mobility, presence of peri-implant disease, problems in esthetics, probing depth and bone loss. Results showed that majority of implant cases are negative to pain, chewing difficulty, mobility, presence of peri-implant disease and problems in esthetics. The results also showed that amount of probing depth and bone loss was less than one-third of the root length. Thus, majority of the implant cases in Metro Manila are considered successful based on the assessment of the implantologists who performed the cases.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dental implants